(untitled) (Journal of the College of Basic Education, 2026)
The study aims to identify "the effect of the academic debate strategy on developing the expressive performance skills of second-grade intermediate school students". To achieve the study objective, the following two hypotheses were formulated: 1.There is a statistically significant difference at the 0.05 level between the mean scores of the pre- and post-tests on expressive performance skills for students in the control group who studied according to the debate strategy and the mean scores of students in the control group who studied the same subject using the traditional method on the expressive performance skills test. 2.There is no statistically significant difference at the 0.05 level between the mean scores of the pre- and post-tests on expressive performance skills for students in the experimental group who studied according to the debate strategy. The researcher adopted a two-group experimental design: a pre-test and a post-test. The sample included (62) female students divided into an experimental group (32) who studied using debates and a control group (30) who studied using the traditional method After controlling for extraneous variables, the researcher prepared an objective and essay test to measure expressive performance skills and verified its validity and reliability. The results showed statistically significant differences in favor of the experimental group, demonstrating the effectiveness of debates in developing expressive skills and fostering creative thinking among female students. The researcher recommended adopting debates in teaching expressive language, encouraging collaborative work and classroom discussions, and holding training courses for teachers on modern teaching strategies. She also suggested expanding the application of debates to other linguistic branches and various educational fields, and conducting comparative studies with modern strategies to evaluate the most effective ones.